Sustainable Development and Higher Education Institutions: Acting with a purpose - Verhoef, Leendert (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Higher education institutions (HEIs) have a unique role and responsibility for the future and for driving the development of a sustainable society. HEIs are charged with the task of fostering sustainability in the leaders of tomorrow, developing solutions and methods for addressing a sustainable future and ensuring that knowledge is contributed to society. HEIs must also ensure that their everyday operations and practices are consistent with a sustainable future, and that they work toward holistically integrating sustainability into both the mission of a university and its daily tasks. This Special Issue builds on papers presented during the 2018 International Sustainable Campus Network Conference and also includes other contributions. The articles reflect the many aspects of sustainability in higher education institutions and illustrate innovation in approach, outcomes, and impact. The papers cover a range of perspectives on sustainability both on and around campuses. These include organization and management issues, networking and city partnership themes, and metrics and indicators related to sustainable development goals. The Special Issue also includes papers on education, student involvement, and gender issues. Select articles include results from surveys and desktop research; others depict approaches on experimentation, living labs, and action research.